Sistem Informasi Monitoring Perkembangan Belajar Anak Usia Dini di PAUD Laskar Pelangi Berbasis Web - Sisilia Susanti Lende; Stefanus D. I. Mau; Alexander Adis (Modem : Jurnal Informatika dan Sains Teknologi., 2026)
This study aims to develop a Student Progress Assessment Information System for PAUD Laskar Pelangi as a solution to various problems that arise in the academic data management process, which was previously carried out manually. The management of student grades, student data, class data, and subject data often encountered obstacles such as delays, recording errors, difficulty in searching for data, and inaccuracies in report preparation. To overcome these issues, a web-based information system was developed to manage all data in an integrated and more efficient manner. The system development method used the Website Development Life Cycle approach, and the application was implemented using the PHP programming language. The system is designed to enable the admin to manage student data, class data, subject data, grades, and automatically generate student grade reports. Database implementation was carried out to ensure that data is stored properly and can be accessed easily. Functional testing was conducted to ensure that all features operate according to user needs. The results of the study show that the developed information system is capable of improving administrative efficiency, accelerating the grade processing workflow, minimizing recording errors, and generating student grade reports quickly and accurately. Therefore, this system provides significant benefits for PAUD Laskar Pelangi in improving the effectiveness of academic administrative management and can be further developed according to the school's needs.